The cost effective role of Eschmarch tourniquet and psychosocial awareness of disease as a key factor in decompressive therapy of filarial lymphedema - Mane, Arun Y.; Naik, Narendra G. (International Surgery Journal, 2019)
Background: The filiariasis is the most common cause of secondary lymphedema of the lower limb. Due to poor awareness of this disease in the people of the lower socioeconomic strata, the patient understands the importance of conservative modality of therapy very late. The cutaneous changes and its complications develop in patient due to unawareness about the nature of noncurable progressive disease. The self-negligence to their own limb also contributes to increase in the morbidity of the disease. The article discusses about cost effective role of Eschmarch tourniquet as a decompressive therapy. The disease causes socioeconomic impairments, stigmatization due to elephantiasis and job insecurity due to cosmetic and functional disability. Methods: This was a retrospective study done in 28 cases of filarial lymphedema. All patients received limb elevation and decompressive therapy by Eschmarch tourniquet. Results: Out of 28 cases, 14 cases in study group of filarial lymphedema with pitting edema (71.42%) and non-pitting edema feet with minimal cutaneous changes (28.57%) showed significant reduction in size of limb girth and satisfactory fluctuating limb girth during the follow up period in OPD respectively, by adequate limb elevation, elastic stockinet and decompressive therapy by Eschmarch tourniquet as compared to the remaining 14 patients of control who received only limb elevation. The better follow up results are noticed by proper guidance to the patient about the disease and its conservative modality of treatment. Conclusions: It is a challenge for the treating consultant to create early awareness about the nature of the filarial disease and early guidance about the conservative treatment which helps to restrict the rapid growth of limb size in filiariatic lymphedema. The eschmarch tourniquet is one of the cost effective decompressive therapy.